Pengaplikasian Matlab pada Perhitungan Matriks - muhamad fatwa; Ristu Rizki; pandiangan sriwinarty; edi supriyadi (Papanda Journal of Mathematics and Science Research, 2022)
This study aims to determine the Application of Matlab in the Matrix. The development and presence of computer technology have made it easy for various parties to use it in life, including education, to support education. Computers are increasingly providing significant benefits in education, especially in learning. Hundreds or even thousands of computer application programs or software can be used for learning mathematics, especially the Matrix. One software that can be used in Matrix learning is the Matrix Laboratory (MATLAB). This program can increase speed and accuracy in mathematical calculations in Matrix learning so that the time needed to work is more efficient. The results obtained are more accurate than estimates done manually. It can also visualize graphs in 2 and three dimensions, for example, in completing the Matrix, so it is expected to increase understanding of the material provided.